In Vivo Detection of Neurofibrillary Tangles by 18F-MK-6240 PET/MR in Patients With Ischemic Stroke. (3rd January 2023) - Michiels, Laura; Thijs, Liselot; Mertens, Nathalie; Sunaert, Stefan; Vandenbulcke, Mathieu; Bormans, Guy; Verheyden, Geert; Koole, Michel; Van Laere, Koen; Lemmens, Robin
Abstract : Background and Objectives: The risk of developing Alzheimer disease is increased after stroke, and this association may not solely be driven by traditional vascular risk factors. Neuronal death leads to the release of tau proteins, which can become dephosphorylated, rephosphorylated, or hyperphosphorylated in the setting of ischemia, possibly leading to formation of neurofibrillary tangles (NFT). Therefore, a potential synergistic effect between development of tauopathy and cerebrovascular lesion burden may contribute to cognitive decline after stroke. We explored the spatial and temporal distribution of NFT after ischemic stroke in vivo by using 18 F-MK-6240 PET. Methods: We included patients with a first ischemic stroke to undergo longitudinal 18 F-MK-6240 PET/MR within 2–4 weeks and 6 months after stroke. For cross-sectional analyses, we also included age-matched healthy controls. We delineated 5 volumes of interest based on T2 FLAIR and T1 MR data: the ischemic lesion, 3 consecutive peri-ischemic areas, and the remaining ipsilesional hemisphere. We performed region-based voxel-wise partial volume correction on the PET data and calculated standardized uptake value ratios (SUVRs) with the cerebellum as the reference region. Results: We did not quantify PET scans of patients within the first month after stroke (n = 17; median age 73 years [interquartile range IQR: 62–82 years]) because the signal intensity was influenced by blood-brain barrier breakdown hampering a reliable data analysis. At 6 months after the event (n = 13; median age 71 years [IQR: 60–79 years]), 18 F-MK-6240 SUVR was increased in the ischemic lesion compared with 20 age-matched healthy controls (median age 71.5 years [IQR: 66–76 years]; ratiolesion/controls = 1.62 ± 0.54; 1-sample t test: p = 0.0015) and gradually decreased in the surrounding tissue (1-way within-subject analysis of variance [F{1.2, 14.8} = 18.0, p = 0.00043]). Discussion: These findings suggest that NFT may form after ischemic stroke and spread in the peri-ischemic brain parenchyma. Further follow-up is required to gain more insight into the spatial and temporal dynamics of this tauopathy after ischemic stroke.